Pengaruh Pengetahuan, Tingkat Pendapatan, dan Tingkat Pendidikan Terhadap Minat Masyarakat Berwakaf Uang - Diana Yulianti (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2020)
This study aims to analysis the effect of knowledge, income level, and education level on the interest of the money-wavering community (North Jakarta city community) and its overview from an Islamic point of view. The population in this study is the Community of the City of North Jakarta. The sampling technique used is probability sampling. The number of respondents in this study were 120 respondents. Data were collected using a questionnaire method. The data analysis method used is the SEM analysis method which is supported by the Smart PLS application. The results showed that: (1) the variable Knowledge has a positive and significant effect on the Interest of Money Waqf Community. (2) Income Level has a positive and significant effect on the Interest of the Money Waqf Community. (3) The the level of education has a negative and insignificant effect on the interest of the money-donated community. The adj value of R2 is 0,66 or 66%. It can be said that the independent variable can explain the variation in the interest of the money-donated community by 66% or in other words knowledge, income level, and money. the level of education can affect the interest of people with donated money by 66%.